2020
DOI: 10.1136/bjophthalmol-2020-317608
|View full text |Cite
|
Sign up to set email alerts
|

Eye bank versus surgeon prepared DMEK tissues: influence on adhesion and re-bubbling rate

Abstract: AimTo investigate the difference in adhesion and rebubbling rate between eye bank and surgeon prepared Descemet membrane endothelial keratoplasty (DMEK) tissues.MethodsLaboratory and clinical retrospective comparative interventional case series. Research corneal tissues were obtained for laboratory investigation. The clinical study involved patients with endothelial dysfunction who underwent DMEK surgery and tamponade with air. Tissues were stripped using a standard DMEK stripping technique (SCUBA) and shipped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 21 publications
1
31
2
1
Order By: Relevance
“…In the pre-loaded DSAEK group, the lenticular stroma is exposed to the transport medium to a greater extent than surgeon cut and this may lead to deposition of the dextran, which may interact with the interfacial matrix on the surface. This may potentially interfere with attachment as has been postulated by Romano et al 13 However, as we did not demonstrate significance, we are unable to conclude this finding. In the literature we found that the effect of transport and processing time, and stromal exposure to dextran on graft characteristics to be negligible.…”
Section: Discussioncontrasting
confidence: 66%
“…In the pre-loaded DSAEK group, the lenticular stroma is exposed to the transport medium to a greater extent than surgeon cut and this may lead to deposition of the dextran, which may interact with the interfacial matrix on the surface. This may potentially interfere with attachment as has been postulated by Romano et al 13 However, as we did not demonstrate significance, we are unable to conclude this finding. In the literature we found that the effect of transport and processing time, and stromal exposure to dextran on graft characteristics to be negligible.…”
Section: Discussioncontrasting
confidence: 66%
“…The concept of “endothelium-in” DMEK insertion techniques have been recently introduced ( 33 – 37 , 44 , 45 ). The grafts are folded, usually in a trifold, with the endothelium on the inside.…”
Section: Discussionmentioning
confidence: 99%
“…These factors in “endothelium-in” techniques reduce the technical difficulties of intracameral graft orientation and unscrolling, making DMEK procedures more controlled and predictable. Some of these “endothelium-in” techniques also use devices created to mimic DSAEK techniques, which many corneal surgeons are accustomed to ( 33 , 44 , 45 ). Various laboratory studies have reported no significant differences in endothelial cell loss when DMEK grafts were loaded “endothelium-in” and pulled-through or loaded “endothelium-out” and injected-through different graft insertion devices ( 62 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies explored different factors that affect DMEK graft elasticity: Romano et al 19 reported decreased adhesion forces in prestripped and preloaded DMEK tissue in dextran-based media in comparison with surgeon-stripped DMEK grafts. Moreover, the DMEK graft detachment rate after the surgery was significantly higher in a prestripped and preloaded DMEK tissue group.…”
Section: Discussionmentioning
confidence: 99%